Fabrication of an effectual, stable and reusable Mg-doped CdAl2O4 nanoparticles for photodegradation of toxic pollutants under visible light illumination. (May 2023) - Mahalaxmi, S.; Rajesh, G.; Senthil Kumar, P.; Akilandeswari, S.; Arul Joshua, M.; Uma Shankar, V.; Ramya, M.; Thirumalai, K.; Rangasamy, Gayathri
Abstract: The water contamination caused by discharging extensive organic dyes stuff into water bodies is one of the utmost significant concerns disturbing the environment and human life. CdAl2 O4 spinel materials have been excellent in the elimination of emerging pollutants by the photocatalysis route. These materials, when altered through methods namely doping with Mg ions, have benefits over CdAl2 O4, especially reduced energy gap and light absorbed in the visible region. The XRD established the creation of space group R 3 ‾ with no other phase step being found. The photoluminescence outcomes indicated that Mg-doped CdAl2 O4 nanoparticles had the preventing e − -h + recombination possibility, which was favorable for the photocatalytic process. The Mg (0.075 M)-doped CdAl2 O4 catalyst had higher photocatalytic performance with 94 and 96% removal of two azo (BB and BG) dyes under a mere 90 min visible light irradiation, which indicated enhanced Photodegradation behaviors when compared to other Mg (0.025, 0.050 M)-doped and pure CdAl2 O4 materials. More interestingly, pH 5 was optimum for the Mg (0.075 M)-doped CdAl2 O4 samples photodegradation of both dyes, and the optimum catalyst amount was 5 mg/100 mL. The doped Mg ions influenced the elimination of both dyes by inducing the manufacture of more active species. The Mg (0.075 M)-doped CdAl2 O4 samples is reusable and highly stable with only a 5% reduction in degradation rate after six cycles. Based on the quencher and ESR investigations, the . OH − and h + are described as active species in the removal reaction. We hope our present examinations highlight the possibility of using Mg (0.075 M)-doped CdAl2 O4 product for a broad range of photodegradation applications, also it may be applied for several ecological remediations, surface cleaning devices, foods and pharmaceutical industry applications. Graphical abstract: Image 1 Highlights: Preparation of a novel CdAl2 O4 and Mg-doped CdAl2 O4 nanoparticles under a co-precipitation approach. Mg-doped CdAl2 O4 products slightly increase and reduce the energy gap compared to pure. The PL emission spectra of the pure CdAl2 O4 and Mg-doped CdAl2 O4 nanoparticles exhibited some defect or oxygen vacancies. ESR and Reactive species tests suggested that h + and . OH − played significant roles in the BB and BG photocatalytic process. The Mg (0.075 M) doped CdAl2 O4 catalyst exhibit substantially high photocatalytic capability.